Analysis of the current status of knowledge, attitudes, and practices among stroke-related healthcare professionals in the treatment of shoulder pain in hemiplegic patients - Bin Huang; Feng Gao (PeerJ)
Objective To investigate the current status of knowledge, attitude, and practice (KAP) of healthcare professionals in stroke-related departments of primary-level tertiary hospitals regarding the prevention and treatment of hemiplegic shoulder pain, and to analyze influencing factors. This aims to provide a reference for further training, guidance, and management of hemiplegic shoulder pain. Methods A total of 123 healthcare professionals from stroke-related departments of two tertiary hospitals in a county-level city in Zhejiang province were selected as the research subjects from March 6, 2023, to March 14, 2023. Written informed consent was obtained from all study participants prior to their inclusion in the study. A questionnaire survey was conducted to assess their KAP status on the prevention and treatment of hemiplegic shoulder pain, and statistical analysis was performed using SPSS 23. Results The scores for knowledge (29.97 ± 9.94), attitude (27.7 ± 2.81), and behavior (29.86 ± 7.86) among the 123 healthcare professionals indicated that department and position were influencing factors for KAP (P < 0.05). Conclusion The overall KAP of healthcare professionals in stroke-related departments of primary hospitals regarding the prevention and treatment of hemiplegic shoulder pain needs improvement. Strengthening relevant knowledge and skills training is necessary to reduce the incidence of hemiplegic shoulder pain and improve patients’ quality of life.